DEMERSAL FISHERY RESOURCES OFF KAKINADA WITH A NOTE ON ECONOMICS OF COMMERCIAL TRAWLING - Narasimham, K A; Rao, G Sudhakara; Sastry, Y Appanna; Venugopalam, W (Indian Journal of Fisheries, 2011)
The trawl fishing industry in the Kakinada area had shown a phenominalgrowth in the past decade. The important demersal fisheries resources during theperiod 1971-74 are given in this paper. The economics of commercial trawling bythe three types of boats operated by the industry are worked out.